The life and travels of Thomas Simpson, the Arctic discoverer [electronic resource] - Simpson, Alexander, b. 1811. (London : R. Bentley, 1845)
Tables. '"Though the sound of fame ."--Childe Harold.' Electronic reproduction. Mode of access: Internet. 44